Internet of Things is a Revolutionary Approach for Future Technology Enhancement: A Review - Nikhat Akhtar; Yusuf Perwej (AG Volumes, 2022)
Bridging the gap between the physical as well as digital world has become an essential part of the modern world. The internet in tandem with the developing technologies plays a significant part in this process. The internet is the common force which unites all technical gadgets in the present day as well as age. Any physical gadget that can be linked to the internet as well as be used to exchange and gather data may be described under the ‘Internet of Things (IoT)’. The future of IoT resides in the potential to change anything as little as a chip or even a whole city into an operational IoT device. This study analyzes the burgeoning subject of IOT with a specific emphasis on the Wireless Multimedia Sensor Network (WMSN) utilized mostly for image acquisition and processing.